Carbohydrate antigen 125, carbohydrate antigen 15–3 and low-density lipoprotein as risk factors for intraocular metastases in postmenopausal breast cancer. Issue 43 (29th October 2021) - Tang, Jing; Yan, Bo; Li, Gao-Feng; Li, Qiu-Yu; Liu, Wen-Feng; Liang, Rong-Bin; Ge, Qian-Min; Shao, Yi
Abstract : Abstract: The prognosis of patients with postmenopausal breast cancer (PBC) could be improved by the early detection of intraocular metastases (IOMs). However, serum biomarkers for IOMs in PBC remain elusive. In the current study, we investigated patients with PBC, and compared serum parameters in an IOM and a non-IOM group, and then differentiated the risk factors related to IOMs. A comparison between an IOM and a non-IOM (NIOM) group was performed using Student t -test and a Chi-Squared test. After constructing a Poisson regression model to identify risk factors, we plotted receiver operating characteristic curves to evaluate the predictive value of significant risk factors in detecting IOMs. The incidence of IOMs in PBC was 1.16%. The histopathology results were not significantly different between the 2 groups. The levels of serum carbohydrate antigen 125 (CA-125), carbohydrate antigen 15–3 (CA15–3) and alkaline phosphatase were significantly elevated in IOMs compared with NIOMs ( P = .082, P < .001, and P < .001, respectively). Compared with NIOMs, age, carbohydrate antigen 19 to 9, hemoglobin, calcium, total cholesterol, low-density lipoprotein (LDL) and apolipoprotein A1 were remarkably lower in IOMs ( P = .038, P < .001, P < .001, P = .032, P = .041, P < .001, and P = .001, respectively). Poisson regression suggested that CA-125, CA15–3 and LDL were contributing to IOMs in PBC as risk factors (OR = 1.003, 95% CI: 1.001–1.005; OR = 1.025, 95% CI: 1.019–1.033; OR = 0.238, 95% CI: 0.112–0.505, respectively). A receiver operating characteristic curve revealed that the cut-off values for CA-125, CA15–3 and LDL were 16.78 0 U/mL, 63.175 U/mL, and 2.415 mmol/L, respectively. The combination of CA-125 and CA15–3 showed significant diagnostic value (area under the curve [AUC] = 0.982, P < .001). Our investigation suggests that CA-125, CA15–3 and LDL remarkably predict IOMs in PBC as risk factors, and the combination of CA-125 and CA15–3 shows considerable diagnostic value.